2018
DOI: 10.1111/apa.14377
|View full text |Cite
|
Sign up to set email alerts
|

Children with a very low birthweight showed poorer reading skills at eight years of age but caught up in most areas by the age of 10

Abstract: Very low birthweight children demonstrated worse reading performance at eight years of age than term-born controls. The gap in reading skills between the groups had largely narrowed two years later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
(43 reference statements)
1
5
3
Order By: Relevance
“…Partial eta squared values indicate that the magnitude of the differences between the groups was really low. Therefore our results do not agree with previous studies carried out with EPT or VPT children in decoding abilities (Anderson et al, 2003;Johnson et al, 2012Johnson et al, , 2016Taylor et al, 2016;Alanko et al, 2017;Guarini et al, 2019), in reading comprehension (Lee et al, 2011) or in decoding abilities and reading comprehension (Pritchard et al, 2009(Pritchard et al, , 2014Johnson et al, 2011;Kovachy et al, 2015;Leijon et al, 2016Leijon et al, , 2018. It is important to note that the evaluation of reading was done at 9 years of age, and at this age children are supposed to be relatively fluent readers.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Partial eta squared values indicate that the magnitude of the differences between the groups was really low. Therefore our results do not agree with previous studies carried out with EPT or VPT children in decoding abilities (Anderson et al, 2003;Johnson et al, 2012Johnson et al, , 2016Taylor et al, 2016;Alanko et al, 2017;Guarini et al, 2019), in reading comprehension (Lee et al, 2011) or in decoding abilities and reading comprehension (Pritchard et al, 2009(Pritchard et al, , 2014Johnson et al, 2011;Kovachy et al, 2015;Leijon et al, 2016Leijon et al, , 2018. It is important to note that the evaluation of reading was done at 9 years of age, and at this age children are supposed to be relatively fluent readers.…”
Section: Discussioncontrasting
confidence: 96%
“…Again, GA does not seem to be the main cause of this difference. These results contrast with those obtained by other studies carried out with VPT and EPT children (Alanko et al, 2017;Leijon et al, 2018;van Houdt et al, 2019), which showed clear deficits in relation to FT children in several EFs; these results support those found by Pérez-Pereira et al (2019) with healthy PT children.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Children who were born with very low birth weights (VLBW) showed poorer reading skills at eight years of age when they were compared with sex and age‐matched term‐born controls, but the gap had narrowed by the age of 10 . Significant catch‐up gains were recorded in phonological awareness, rapid naming and reading comprehension.…”
Section: Children With Very Low Birth Weights Display Poorer Reading mentioning
confidence: 99%